Acoustical investigation of open-plan offices in green buildings in Malaysia - Abd Jalil, Nurul Amira; Che Din, Nazli; Keumala, Nila (2013)
Open-plan office has become the most popular type of office layout. Organizations were inclined to employ open-plan office layout for its economic, flexibility and ideological reasons. Green building tends to utilize this concept of office layout for its ability to assist in maximization of daylight usage and natural ventilation. However reduced barriers in open-plan office resulted in poor acoustical performance. Thus, the objective of this study is to investigate and evaluate the level of acoustical performance of open-plan offices in green buildings in Malaysia. Investigation were limited to selected assessment parameters of background noise (BN) level, noise criteria (NC), reverberation time (RT) and speech transmission index (ST!). The BN levels for all measured open-plan offices were found to be acceptable around 35 dB(A) while the NC ratings found the spaces to be somewhat quiet. RTs were varied from satisfactory 0.7s to an unacceptable 1.5s. STIs were found to be ample within good and fair speech intelligibility. However. it still provides equally ample speech distraction towards the occupants of the spaces.